The Effect Of Transformational Leadership and The Asah Asih Asuh Leadership Model Of The Principal On Teachers’ Professional Competence at SMA Negeri 1 Singkep - Mariono; Tety Kurmalasari; Dody Irawan; Encik Abdulhajar; Nevrita (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study aims to determine the influence of transformational leadership and the Asah Asih Asuh pattern of the school principal on teachers’ professional competence at SMA Negeri 1 Singkep. The Asah Asih Asuh pattern emphasizes intellectual stimulation (asah), affective care (asih), and nurturing guidance (asuh) as the pillars of transformational leadership practiced by the school principal in fostering teacher professionalism. This research employs a quantitative approach with a descriptive-verificative design. The population consists of all teachers at SMA Negeri 1 Singkep, totaling 32 individuals, who were all selected as the research sample (total sampling). Data were collected through questionnaires developed based on indicators of transformational leadership, Asah Asih Asuh values, and teacher professional competence. The data were analyzed using descriptive statistics and regression analysis to determine the extent of influence between variables. The results indicate a significant and positive influence of the principal’s transformational leadership and Asah Asih Asuh pattern on teachers’ professional competence. This finding suggests that principals who demonstrate visionary leadership, emotional intelligence, and a nurturing approach effectively enhance teachers’ ability to plan, implement, and evaluate learning professionally. The study concludes that the Asah Asih Asuh leadership model serves as a strategic framework for improving teacher professional competence in coastal educational contexts. It is recommended that principals continue to develop this model to foster a more collaborative, innovative, and humanistic school culture.